2020
DOI: 10.1038/s41598-020-64947-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a subpopulation of CD133+ cancer stem cells from Chinese patients with oral squamous cell carcinoma

Abstract: Cancer stem cells (CSCs) play a critical role in cancer development and growth. The aim of this study was to identify and isolate cScs from populations of primary oral squamous cell carcinoma (OSCC) cells, which were obtained from OSCC specimens and identified by cell morphology and immunohistochemical staining for keratin. CD133 + cells detected by flow cytometry comprised 0.41 ± 0.06% of primary OSCC cells and were isolated from primary OSCC cell populations using magnetic-activated cell sorting, revealing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…It has a high rate of regional lymphatic metastasis and poor apy drugs, such as cisplatin, have many side effects. Moreover, the chemotherapeutic resistance of tumor cells to cisplatin is increasing (Ma et al, 2020). Therefore, there is urgency to seek new anti-cancer drugs for the intervention of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…It has a high rate of regional lymphatic metastasis and poor apy drugs, such as cisplatin, have many side effects. Moreover, the chemotherapeutic resistance of tumor cells to cisplatin is increasing (Ma et al, 2020). Therefore, there is urgency to seek new anti-cancer drugs for the intervention of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry and immunofluorescence staining were performed as described previously 21 . The detailed procedure is shown in .…”
Section: Methodsmentioning
confidence: 99%
“…Several associations between clinicopathological characteristics and CSCs have been appointed in HNSCC, including tumor size, regional and distant metastases, perineural invasion, radiation failure, and poor disease-free survival [30] . A previous study of our group explored CSCs markers in tongue tumors and found that the overexpression of CD44 was related to worst overall survival, and Nanog and Oct4 were associated with regional metastasis and death [31] . Ma et al suggested that CD133 + cells could be responsible for aggressiveness and chemoresistance in oral tumors [32] .…”
Section: Introductionmentioning
confidence: 99%